(untitled) (The Journal of Psychology and Sociology, 2017)
The article examines the impact of the socialization process in the sense structure of the meaning of life and the meaning of the individual actions in a new social environment. Sense structure of personality for centuries considered to be important components of every life. Meanings form of human relationship to the world and to his personality as a whole. That sense is the guide of life, which creates standards and the existence of the border. The desire for personal growth, self-actualization is the most important to the quality of the individual. Current demand for self-development, self-improvement are an indication of the sense of stability and at the same time a condition to achieve it. Rapid flow of information in the process of globalization does not adhere to the previously installed traditional sense of values. This process of continuous changes made ineffective natural transmission of cultural and historical experience of the older generation to the younger based on the sense of the historical, social, cultural and psychological interaction between members of the same social circle, and the question of change and transformation of meaning is particularly significant. At its core, the question of meaning is increasingly seen as an eternal philosophical problem of human life. But in the modern era of discussion about the meaning and prospects of its development, change, transformation, acquired special importance in all areas of scientific study of man. In psychology, at this stage of the sense structure of modern man particularly relevant, as they affect the value orientation, attitudes, interpersonal and interethnic interaction. According to information received study the sense structure of personality change and transform. Transformation and change the meaning of life associated with the change and transformation of the meaning of action through changes in the meaning of applicable changes or transforms the meaning of life.